The Effect of Tridharma Human Resource Management in Higher Education on Improving the Quality of Private Higher Education Lecturers in Clusters of Higher Schools in DKI Jakarta and West Java Regions - Yusup, Yusup; Sanusi, Achmad; Trisnamansyah, Sutaryat; Muchtar, Hendi Suhendraya (AGUSPATI Research Institute, 2021)
So far the implementation of Tri Dharma Human Resources Management of Universities, a lecturer carries three main tasks, namely: (1) education and teaching; (2) Research; and (3) devotion to the community. The general objective of this study, namely to find out and analyze the influence of the Human Resource Management of Tri Dharma Higher Education on improving the quality of PTS lecturers in the high school cluster in the DKI Jakarta and West Java areas. Interpretation and analysis of the results of the study, obtained general conclusions as follows: (1). There is an Effect of Human Resource Management in the field of education and teaching of improving the quality of lecturers at STKIP Kusumanegara; (2). There is an Effect of Human Resource Management in the field of research on improving the quality of lecturers at STKIP Kusumanegara; (3). There is an Effect of Human Resource Management in the field of service to the public on improving the quality of lecturers at STKIP Kusumanegara; (4). There is an Effect of Human Resource Management in the field of education and teaching, Human Resource Management in the field of research and Human Resource Management in the field of service to the community jointly to improve the quality of lecturers at STKIP Kusumanegara; (5). There is an Effect of Human Resource Management in the field of education and teaching of improving the quality of lecturers at STIE MBI; (6). There is an Effect of Human Resource Management in the field of research on improving the quality of lecturers at STIE MBI; (7). There is an Effect of Human Resource Management in the field of service to the public on improving the quality of lecturers at STIE MBI; (8). There is an Effect of Human Resource Management in the field of education and teaching, Human Resource Management in the field of research and Human Resource Management in the field of service to the community jointly to improve the quality of lecturers at STIE MBI; (9). There is an Effect of Human Resource Management in the field of education and teaching on improving the quality of lecturers at STMIK MIC (10). There is an Effect of Human Resource Management in the field of research on improving the quality of lecturers at STMIK MIC; (11). There is an Effect of Human Resource Management in the field of service to the public on improving the quality of lecturers at STMIK MIC; (12). There is an Effect of Human Resource Management in the field of education and teaching, Human Resource Management in the field of research and Human Resource Management in the field of service to the community jointly to improve the quality of lecturers at STMIK MIC; (13) There are supporting factors and inhibiting the quality of lecturers at STKIP Kusumanegara, STIE MBI, STMIK MIC through the implementation of the Human Resource Management Tri Dharma Higher Education. The findings of the study, namely from the three Tri Dharma components of college, research and publications including difficulties carried out by lecturers, while there are demands to publish the results of their research on reputable international journals that have a significant effect on improving the quality of lecturers.